Defect engineering of low-coordinated metal-organic frameworks (MOFs) for improved CO₂ access and capture - Niu, Jiabin (2023)
While metal-organic frameworks (MOFs) are promising gas adsorbents, their tortuous microporous structures cause additional resistance for gas diffusion, thus hindering the accessibility of interior active sites. Here, we present a practical strategy to incorporate missing cluster defects into a representative low-coordinated MOFs structure, Mg-MOF-74, while maintaining the stability of a defect-rich structure. In this proposed method, graphene oxide (GO) is employed as modulator, and crystallization time is varied to promote defect formation by altering the nucleation and crystal growth processes. The best performing GO-modified Mg-MOF-74 sample (MOF@GO 40 h) achieved 18% and 15% improvement in surface area and total pore volume, respectively, over pristine Mg-MOF-74. The reduced diffusion resistance to gas flow translates to increased accessibility for gas molecules to active Mg adsorption sites inside the MOFs, leading to enhanced CO2 capture performance; the CO2 uptake quantity of MOF@GO 40 h arrives at 6.06 mmol/g at 0.1 bar and at 9.17 mmol/g at 1 bar and 25 °C, 19.29% and 16.37% higher, respectively, than that of the pristine Mg-MOF-74, with a CO2/N2 selectivity around 17.36% greater than that of pristine Mg-MOF-74. Our study demonstrates a facile approach for incorporating defects into MOFs systems with low coordination environments, thus expanding the library of defect-rich MOFs beyond the current highly coordinated MOF systems.